Pengaruh Model Discovery Learninng Terhadap Kemampuan Literasi Sains Peserta Didik - Wulan Aprilia Utami; Rini Rita T Marpaung; Berti Yolida (Universitas Lampung, 2019)
The purpose of this study was to determine the effect of Discovery Learning Models On Students Science Literacy skills on VII grade students of SMP Negeri 35 Bandar Lampung in